Natural coumarins from Murraya paniculata as mixed-type inhibitors of cholinesterases: In vitro and in silico investigations - Khalid, Asaad; Khan, Waqasuddin; Zia, Komal; Azizuddin,; Ahsan, Waquar; Alhazmi, Hassan A.; Abdalla, Ashraf N.; Najmi, Asim; Khan, Andleeb; Bouyahya, Abdelhakim; Ul-Haq, Zaheer; Khan, Ajmal (Frontiers in Pharmacology, 2023)
Currently, acetylcholinesterase (AChE) inhibiting drugs in clinical use, such as tacrine, donepezil, rivastigmine, and galanthamine, are associated with serious side effects and short half-lives. In recent years, numerous phytochemicals have been identified as inhibitors of cholinesterases with potential applications in the management of Alzheimer's disease (AD). In this study three natural coumarins, 2'-O-ethylmurrangatin (1), murranganone (2), and paniculatin (3) isolated previously by our group from the leaves of Murraya paniculata, were tested against the two cholinesterases (ChE) enzymes, AChE and butyrylcholinesterase (BChE) using in vitro assay. Molecular docking was performed to highlight the structural properties that contribute to the molecular recognition pattern in the inhibition of ChE and the structural differences resulting in the selectivity of these compounds toward AChE. Classical enzyme inhibition kinetics data suggested that compounds 2 and 3 were potent inhibitors of AChE and BChE having non-competitive and mixed-type behavior, while 1 was found inactive against both enzymes. The findings from molecular docking studies revealed the competitive and non-competitive inhibition mechanisms of compounds 2 and 3 against both enzymes. Molecular docking and simulations have revealed that hydrogen bonding, mediated by ketone and hydroxyl functionalities in various positions, significantly contributes to the binding of the inhibitor to the receptor. According to MD simulation studies, the stability of the ligand-AChE complex for the most active compound (3) is found to be comparable to that of the widely used drug Tacrine. In addition, to evaluate the drug-likeness of compounds, in silico ADME evaluation was performed, and the compounds presented good ADME profiles. Data suggested that the coumarin nucleus having diverse side chains at the C-8 position can serve as a potential inhibitor of cholinesterases and can act as a lead to develop a new semisynthetic drug for the treatment of AD.